The Effect of Plant growth-promoting Rhizobacteria on the growth of eggplant seedlings and the tolerance to transplant shock - متيادي بوراس; ياسر حماد; ابراهيم امهنا (Latakia University Journal -Biological Sciences Series, 2022)
This experiment was carried out in greenhouse conditions (unheated) in April 2021, The eggplant seeds were sown in peat-moss in pots (8 cm in diameter) to study the influence of a mixture of Plant growth-promoting rhizobacteria (PGPR) in the quality of eggplant seedlings and their tolerance to transplant shock. Emerald F1 eggplant hybrid, and bacterial bio-fertilizer consisting of the following bacterial species: Azotobacter chroococcom, Pseudomonas fluorescence, Bacillus circulas, Rhizobium phaseoli, were used in the research. The experiment included four treatments: Control (untreated plants), Seed-dipping, seedlings soil drench, and Seed-dipping and re-inoculation by drenching (15× 109 CFU mL−1 per plant; one treatment). The experiment was designed according to the complete randomized design which included (4) treatments, each treatment included (3) replicates and each replicate included (15) plants. The results showed that Seed-dipping and re-inoculation by drenching seedlings soil was significantly superior to the other treatments Seed-dipping, seedlings soil drench) and achieved the best results compared with the control, where it recorded: plant height (32.2 cm), stem diameter (6.9 mm), number of leaves (8.3 leaves/plant), leaf area (267 cm2), and the wet weight of the shoot and root were (39.4 g) and (7.1 g), respectively, compared to (26 cm) and (4.9 mm) and (5.3 leaves/plant) and ( 81.7 cm²), (21.1 g) and (2.8 g) respectively for plant height, stem diameter, number of leaves, leaf surface area, and wet weight of shoot and root of control plants.